INFLUENCE OF BIOLOGICAL PRODUCTS AND MICROFERTILIZERS IN FORMATION OF YIELD OF PEA SEEDS - Vuiko, O. M. (Scientific Progress & Innovations, 2022)
Peas in Ukraine are mainly export-oriented crops, as the largest share of the crop is supplied to foreign markets, while domestic consumption, as in other segments, is stagnant. For a long time the pea market in Ukraine lobbied and gained momentum, encouraging farmers to bet on it, especially since the crop is quite profitable and has proven itself well in crop rotation. However, in recent years there has been relatively low growth rates and low stability of productivity of cenoses of legumes. If in 1992 the sown area of peas in Ukraine exceeded one million hectares, in 2020 not even half of this figure was sown. However, in order to increase profitability, it is necessary to introduce pea growing technologies that would provide much higher yields than those obtained by farmers in recent years. It is quite possible to increase it to 50 centers’ per hectare and more, as evidenced by the experience of European countries. This is primarily due to the fact that peas significantly reduce their productivity in adverse weather conditions and unbalanced nutrients. Optimal feeding conditions, in turn, ensure the formation of a fairly high yield and grain quality and, at the same time, significantly reduce the negative impact of weather conditions. Growing legumes is an extremely important factor in creating an effective mechanism for increasing soil fertility based on the accumulation of atmospheric nitrogen and the accumulation of organic matter to enhance humification processes. In the technology of growing each crop, each of its elements is important. The review presents a modern analysis of data from literature sources on the characteristics of peas, their yield and structure of sown areas. The peculiarities of the formation and functioning of the symbiotic apparatus of peas are described; some modern biological preparations and microfertilizers are given. The influence of biological products and microfertilizers on yield formation, their importance in the course of physiological processes in pea plants is considered. The key phases of growth and development of plants in which they need micronutrients the most have been identified. It is noted that the prospect of increasing productive pea crops to create optimal balanced for all elements of the nutritional conditions and stimulate nitrogen fixation.